Recall responses to tetanus and diphtheria vaccination are frequently insufficient in elderly persons. - Birgit Weinberger (Public Library of Science (PLoS), 2013)
Unlabelled Demographic changes and a more active life-style in older age have contributed to an increasing public awareness of the need for lifelong vaccination. Currently many older persons have been vaccinated against selected pathogens during childhood but lack regular booster immunizations. The impact of regular vaccinations when started late in life was analyzed in an open, explorative trial by evaluating the immune response against tetanus and diphtheria in healthy older individuals. 252 persons aged above 60 years received a booster vaccination against tetanus, diphtheria, pertussis and polio and a subcohort (n=87) was recruited to receive a second booster vaccination against tetanus, diphtheria and pertussis 5 years later. The percentage of unprotected individuals at the time of enrollment differed substantially for tetanus (12%) and diphtheria (65%). Despite protective antibody concentrations 4 weeks after the first vaccination in almost all vaccinees, antibodies had again dropped below protective levels in 10% (tetanus) and 45% (diphtheria) of the cohort after 5 years. Protection was restored in almost all vaccinees after the second vaccination. No correlation between tetanus- and diphtheria-specific responses was observed, and antibody concentrations were not associated with age-related changes in the T cell repertoire, inflammatory parameters, or CMV-seropositivity suggesting that there was no general biological "non-responder type." Post-vaccination antibody concentrations depended on pre-existing plasma cells and B cell memory as indicated by a strong positive relationship between post-vaccination antibodies and pre-vaccination antibodies as well as antibody-secreting cells. In contrast, antigen-specific T cell responses were not or only weakly associated with antibody concentrations. In conclusion, our findings demonstrate that single shot vaccinations against tetanus and/or diphtheria do not lead to long-lasting immunity in many elderly persons despite administration at relatively short intervals. Sufficient antigen-specific B cell memory B generated by adequate priming and consecutive booster vaccinations and/or exposure is a prerequisite for long-term protection. Trial registration EU Clinical Trials Register (EU-CTR); EudraCT number 2009-011742-26; www.clinicaltrialsregister.eu/ctr-search/trial/2009-011742-26/AT.